Essays in industrial econometrics - Klein, Lawrence R. (Philadelphia : Economics Research Unit, University of Pennsylvania, 1969)
Here is a major effort to apply econometric techniques to model the activities of separate industries in the United States, using annual or quarterly data for various sample periods from 1948 to 1966. Volume I contains two studies of the American car industry, the first by Ueno and Tsurumi, an aggregate study of car demand and supply, the second a dis-aggregated study of the individual behaviour of the five separate car firms in the American industry. The second study, by Tsurumi, is described as a study of oligopolistic competition. A third study in Volume I is of petroleum refinery operations by Adams and Griffin.
Vol. 1-3
Includes bibliographical references.
rpm 18/10/2017
Loans
Keywords: Industrial economics; Industries --Econometrics